Appropriating technology for accountability: messages from Making All Voices Count - McGee, Rosemary; Edwards, Duncan; Hudson, Hannah; Anderson, Colin; Feruglio, Francesca (IDS, 2018)
Making All Voices Count was a programme designed to solve the ‘grand c hallenge’ of creating more effective democratic governance and account ability around the world. It used funding from four donors to support the development and spread of innovative ideas for solving governance problems – many of them involving tools and platforms based on mobile phone and web technologies. Between 2013 and 2017, the programme made grants for innovation and scaling projects that aimed to amplify the v oices of citizens and enable governments to listen and respond. It als o conducted research and issued research grants to explore the roles t hat technology can play in securing responsive, accountable government and building an evidence base. This synthesis report reviews the Maki ng All Voices Count’s four-and-a-half years of operational experience and learning. It shares 14 key messages on the roles technologies can play in enabling citizen voice and accountable and responsive governan ce. These messages are presented in four sections: (1) Applying techno logies as technical fixes to solve service delivery problems; (2) Appl ying technologies to broader, systemic governance challenges ; (3) App lying technologies to build the foundations of democratic and accounta ble governance systems; (4) Applying technologies for the public ‘bad’ , when tech can be dangerous for democracy. The tech optimism of the e ra in which the programme was conceived can now be reappraised from th e better-informed vantage point of hindsight. Making All Voices Count’ s wealth of diverse and grounded experience and documentation provides an evidence base that should enable a more sober and mature position of tech realism as the field of tech for accountable governance contin ues to evolve.